Depth-dependent refractive index of normal and early degenerated articular cartilage - Wang, K.; Wu, Jianping; Kirk, Thomas (SPIE, 2013)
The depth distributions of refractive index (RI) in normal and early degenerated articular cartilage (AC) were measured and correlated to the pathological statuses. Utilizing a confocal microscope, the depth distribution of RI was determined with an interval of 50µm from the articular surface and approximated as a smooth curve. The fluctuation of RI was quantified with a specially defined coefficient and the proteoglycan (PG) loss was quantified with histological images. The overall RI of the AC collected from the femoral condyles of mature sheep was 1.4444. Significant differences existed in the refractive indices of different cartilage samples or even in the different depths of the same sample. The RI of normal cartilage distributed as a regular ramp or arch curve with depth and peaked in the middle-deep zone. The cartilage samples detected with high PG losses were coupled with severe fluctuations of RI. The fluctuating level was increased with pathological progress. The coefficient of RI fluctuation can distinguish the normal cartilage from the initially degenerated one, which potentially provides an indicator to detect the pathological development of AC.